2018
DOI: 10.1371/journal.pone.0203439
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal penile nerve block versus eutectic mixture of local anesthetics cream for pain relief in infants during circumcision: A meta-analysis

Abstract: ObjectiveTo compare dorsal penile nerve block (DPNB) and eutectic mixture of local anesthetics (EMLA) cream for pain relief in infants during circumcision.MethodsWe systematically searched Medline via PubMed, Embase, CNKI and the Cochrane Library Center Register to identify randomized controlled trials up to March 2018. Effect estimates were performed in random effect models. Mean neonate infant pain scale (NIPS) scores, incidence of hematoma, edema and erythema, mean heart rate were conducted to assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(23 reference statements)
0
12
0
1
Order By: Relevance
“…Como es más fácil de realizar y con mejor perfil de EA podría ser prefererido sobre éstos [24]. -bloqueo de nervio dorsal del pene: Su uso en cirugía ambulatoria es frecuente en circunsiciones o cirugía de fimosis/parafimosis, donde ha demostrado efectividad superior a la analgesia tópica, sin embargo, se ha asociado a mayor tasa de complicaciones como hematomas [25]. -bloqueos para cirugía otorrinolaringológica: En tonsilectomías se pueden realizar bloqueos locales en la fosa tonsilar o bloqueo del nervio glosofaríngeo.…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified
“…Como es más fácil de realizar y con mejor perfil de EA podría ser prefererido sobre éstos [24]. -bloqueo de nervio dorsal del pene: Su uso en cirugía ambulatoria es frecuente en circunsiciones o cirugía de fimosis/parafimosis, donde ha demostrado efectividad superior a la analgesia tópica, sin embargo, se ha asociado a mayor tasa de complicaciones como hematomas [25]. -bloqueos para cirugía otorrinolaringológica: En tonsilectomías se pueden realizar bloqueos locales en la fosa tonsilar o bloqueo del nervio glosofaríngeo.…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified
“…Some use topical analgesia such as lidocaine; others prefer nerve block. A recent meta-analysis has concluded that the dorsal penile nerve block was far more effective in pain control than a mixture of local anesthetics in infants during circumcision [13]. Local analgesics, though they may have fewer complications, are unpredictable.…”
Section: Complications Related To Anesthesiamentioning
confidence: 99%
“…Nerve injuries might occur secondary to intraneural injection. An allergic reaction might happen in the form of Urticaria or anaphylaxis, with the worst outcome being systemic anesthetic toxicity when accidentally injecting the local anesthetic in the systemic circulation [13].…”
Section: Complications Related To Anesthesiamentioning
confidence: 99%
“…Circumcision of boys is one of the most common operations performed by pediatric surgeons, and although it is performed daily, it can cause fear and anxiety in children. Therefore, anesthesia management is very important in this patient group [1,2]. Postoperative pain management is important.…”
Section: Introductionmentioning
confidence: 99%
“…Re-gional anesthesia techniques are also used for postoperative analgesia in pediatric patients. Caudal epidural anesthesia (CEA) is accepted as the gold standard for postoperative pain control after lower abdominal and perineal pediatric surgeries [1,2]. Although CEA is highly effective and safe, its use can lead to complications related to dural damage, its ability to cause a motor block in the lower extremities, and impairment of bladder function, so limiting its use [3,4].…”
Section: Introductionmentioning
confidence: 99%